2020
DOI: 10.1177/2055102920917250
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of chronic pain intensity and disability among adults with sickle cell disease

Abstract: Among 170 adults with sickle cell disease, we evaluated chronic pain impact and disability prevalence, assessed age and gender differences, and identified psychosocial predictors of chronic pain intensity and disability. Most participants had a high level of disability. Chronic pain intensity and disability were significantly associated with pain catastrophizing and chronic pain self-efficacy, and worsened with age. Further research is needed to confirm study findings and develop interventions, including palli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…A biopsychosocial model of chronic pain has been widely adopted, and epidemiologic studies suggested that chronic pain increases the risk for depression, anxiety, and pain catastrophizing [ 20 , 21 ]. The coexistence of chronic pain and emotional disorders initiates vicious pain, which spirals and amplifies depression and pain catastrophizing and then disturbs daily activities and consequently further exacerbates pain [ 32 34 ]. Depression is a leading cause of disability globally.…”
Section: Discussionmentioning
confidence: 99%
“…A biopsychosocial model of chronic pain has been widely adopted, and epidemiologic studies suggested that chronic pain increases the risk for depression, anxiety, and pain catastrophizing [ 20 , 21 ]. The coexistence of chronic pain and emotional disorders initiates vicious pain, which spirals and amplifies depression and pain catastrophizing and then disturbs daily activities and consequently further exacerbates pain [ 32 34 ]. Depression is a leading cause of disability globally.…”
Section: Discussionmentioning
confidence: 99%
“…After obtaining research ethics approval and informed consent, a descriptive, cross-sectional, survey study investigated chronic pain and disability among 170 Black adults with SCD. They were recruited from a sickle cell center between March 2018 and July 2019 (Matthie et al, 2020). Participant inclusion criteria were 18–40 years of age, diagnosis of SCD, three or more days of pain experienced each week, and ability to read, write, and understand English.…”
Section: Methodsmentioning
confidence: 99%
“…We will examine heterogeneity both in the subject matter of included studies (context, intervention and outcomes) and in the reported effect sizes (visually and using I 2 ) (Matthie et al, 2020 ). If meta‐analysis is appropriate, we will calculate an inverse variance weighted average effect size using a random effects model.…”
Section: Methodsmentioning
confidence: 99%